2013
DOI: 10.1016/j.jcmg.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Carotid Disease on Ultrasound and Coronary Disease on CT Angiography

Abstract: Carotid plaque and increased carotid IMT are associated with the presence and severity of coronary calcification and disease on CTA in ambulatory subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
54
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 30 publications
6
54
2
6
Order By: Relevance
“…1,2 The progression of atherosclerosis in the arteries can cause myocardial and cerebral infarction, which is a great burden to the global aging society. 3 The correlation between coronary and extracranial artery atherosclerosis has been extensively explored in previous studies that reported a positive interrelation in atherosclerotic burden 4,5 and clinical events 6-9 between 2 arteries. However, relatively little is known about the association between coronary and intracranial artery atherosclerosis.…”
mentioning
confidence: 99%
“…1,2 The progression of atherosclerosis in the arteries can cause myocardial and cerebral infarction, which is a great burden to the global aging society. 3 The correlation between coronary and extracranial artery atherosclerosis has been extensively explored in previous studies that reported a positive interrelation in atherosclerotic burden 4,5 and clinical events 6-9 between 2 arteries. However, relatively little is known about the association between coronary and intracranial artery atherosclerosis.…”
mentioning
confidence: 99%
“…18,20,21,23 It is possible that these coronary calcification studies observed a part corresponding to the previously mentioned first half in the carotid calcium formation, in particular, a rising symptomatic rate until the calcium score of 400. It is conceivable that carotid arteries that have larger vascular walls can hold more calcification or calcified nodules 37 with higher calcium scores than coronary arteries that have smaller walls.…”
Section: Discussionmentioning
confidence: 87%
“…22 Carotid intima-media thickness and plaque were also revealed to be associated with the presence and severity of coronary calcification and disease. 23 Concerning carotid artery calcification, however, most studies have suggested an inverse relationship between calcified carotid plaques and stroke or neurologic symptomatology, 2,7,24,25 although conflicting data have been reported. 26,27 These differences in outcomes have been ascribed to differences in vascular bed distribution and plaque types between coronary and carotid atherosclerosis, 28 but no convincing explanation has been demonstrated to date.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study conducted by Cohen et al (33) compared the presence of carotid disease, evaluated using ultrasonography, and the presence of CAD, evaluated using CCTA. It showed that carotid plaque, in conjunction with C-IMT, correlates closely with the severity of coronary calcifications identified using CCTA.…”
Section: Discussionmentioning
confidence: 99%